DIAGNOSIS AND TREATMENT OF MICRONUTRIENT DEFICIENCIES IN CHILDREN WITH INTESTINAL PARASITES - Saidova Firuza Salomovna; Sanakulov Dilmurod Tulkinovich (Galaxy International Interdisciplinary Research Journal, 2023)
Intestinal parasites remain one of the most common problems of special medical, social and economic importance among children worldwide.Micronutrient deficiency among children with intestinal parasitosis is dangerous and causes complications, so early diagnosis and treatment are of practical importance. Providing drugs to risk groups reduces the intensity of intestinal helminth infections. Treatment of intestinal worms among children of preschool age is carried out seasonally in preschool educational institutions.